PENGARUH JUMLAH KUNJUNGAN WISATAWAN, KURS DOLLAR, DAN EKSPOR KOMPONEN RUMAH JADI BALI TERHADAP PDRB DI PROVINSI BALI - Devi, Ni Putu Kiki Sita; Aswitari, dan, Luh Putu; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 7 (2020): VOL 9 NO 7, JULI 2020 (1431-1630), 2020)
A region is advanced if the economic growth is a good as seen from the regional income indicators. T he government economic observers, business and the public are concerned about the up and down of economic growth. Trade activities, production levels, inflation and the other factors that affect fluctuating economic growth conditions. The purpose of this study are (1) To analyze the simultaneous influence of the number of tourist visits, the dollar exchange rate , and the export of components of Bali finished houses to GRDP in Bali Province (2) To analyze the partial y effect of number of tourist visits, dollar exchange rates and exports of components of finished Bali houses to GDP in Bali province. The data used are secondary data, and the analysis technique used is the Multiple Linear Regression analysis technique. The results showed that (1) The Number of Tourist Visits, Dollar Exchange Rates, and Exports The components of Bali finished houses simultaneously influence the GRDP in Bali Province, (2) The Number of Tourist Visits and The Export of Bali House Components has a positive and significant effect on GRDP in Bali Province, (3) Dollar Exchange Rates does not have a negative effect on GRDP in Bali Province . Keywords : the number of tourist visits, the dollar exchange rate, exports of components of houses to Bali, GRDP